2003
DOI: 10.1038/sj.ejcn.1601594
|View full text |Cite
|
Sign up to set email alerts
|

Iron status at 12 months of age — effects of body size, growth and diet in a population with high birth weight

Abstract: Objective: To investigate effects of growth and food intake in infancy on iron status at the age of 12 months in a population with high birth weight and high frequency of breast-feeding. Design: In a longitudinal observational study infants' consumption and growth were recorded. Weighed 2 day food records at the ages of 6, 9 and 12 months were used to analyse food and nutrient intake. Setting: Healthy-born participants were recruited from four maternity wards. Blood samples and growth data were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
140
8
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(175 citation statements)
references
References 45 publications
18
140
8
9
Order By: Relevance
“…A gender difference in the iron status was not seen in the present study, in contrast to previous findings in Icelandic 1-y-olds (Thorsdottir et al, 2003), where boys had significantly worse iron status and were more likely to be irondeficient than girls. Domellof et al (2002) concluded from their study of 9-month-old children, that difference in SF and MCV values was to be expected between boys and girls due to genetic or hormonal variances and sex-specific cutoffs for these indices might therefore be needed.…”
Section: Iron Status In 2-year-old Icelandic Children Bs Gunnarsson Econtrasting
confidence: 99%
See 4 more Smart Citations
“…A gender difference in the iron status was not seen in the present study, in contrast to previous findings in Icelandic 1-y-olds (Thorsdottir et al, 2003), where boys had significantly worse iron status and were more likely to be irondeficient than girls. Domellof et al (2002) concluded from their study of 9-month-old children, that difference in SF and MCV values was to be expected between boys and girls due to genetic or hormonal variances and sex-specific cutoffs for these indices might therefore be needed.…”
Section: Iron Status In 2-year-old Icelandic Children Bs Gunnarsson Econtrasting
confidence: 99%
“…These are approximately half of the percentages seen in Icelandic 1-y-olds, with the same criteria used for defining iron deficiency and iron-deficiency anaemia, also fewer 2-y-olds had depleted iron stores (SFo12 mg/ l), or 27%, compared to 41% of 1-y-old children (Thorsdottir et al, 2003). However, the present findings show slightly worse iron status than observed in other recent studies of children in this age group from other Nordic countries.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations